IMPLEMENTASI METODE DEMPSTER SHAFER PADA SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT TROPIS - Siregar, Ratu Mutiara (The Indonesian Journal of Computer Science, 2024)
Tropical diseases are various infectious diseases that occur frequently in tropical and subtropical regions. These diseases can be caused by infections from viruses, bacteria, fungi, and parasites, and are usually transmitted through vectors or direct contact. In Indonesia, some common tropical diseases include dengue fever, malaria, elephantiasis, tuberculosis, worm infections, and fungal infections. Understanding tropical diseases is crucial to finding ways to diagnose and treat them. Therefore, one method that can be used in this research is the expert system based on the Dempster-Shafer method. This method can be used to diagnose tropical diseases with high accuracy, thus enabling more effective treatment and prevention. The expert system using the Dempster-Shafer method is designed using symptom data of tropical diseases collected from an expert. The result obtained from this research is a system that functions to solve problems and provide information about diseases along with symptoms experienced by the user. By using a web-based system as access for the public, it becomes easier for them to obtain accurate results and information.